DESAIN BALANCED SCORECARD SEBAGAI STRATEGI UNTUK MENUJU PROGRAM STUDI BERKELAS DUNIA Studi Kasus: Program Studi Teknik Mesin, Universitas XYZ - suhendin (LIAISON JOURNAL OF BEST, 2024)
Becoming a world class study program is not achieved by self-declaration; rather, this prestige status is conferred by the outside world on the basis of international recognition. It needs a strategy to become a world class study program. One strategy that can be adopted by a study program is to design a Balanced Scorecard, which provides guidance for decision makers to design Objective Performance, Measures, planning the achievement of set targets, and arranging strategic initiatives for achieving the target though four Perspectives. The four perspectives are: a financial perspective, a customer/stakeholder perspective, an internal business process perspective, and growth and learning perspective. After measuring to the four perspectives in XYZ study program, the result of financial performance, customer/stakeholder satisfaction performance, and internal business process performance is still not enough to achieve world-class study program status. The average of three scores is not far from 50% from the target. While growth and learning performance, score is 73% from the target. So, they need a variety of strategic initiatives to improve the performance of the four in order to achieve the targets set. With the increasing performance of the four perspectives, it will be able to improve the overall performance of the institution. This increase is of course in accordance with the targets and measures set to achieve a world-class study program. Keywords: Balanced Scorecard Financial Perspective, Customer/stakeholder Perspective, Internal Business Process Perspective, Growth and Learning Perspective